ANALISIS PENGARUH INOVASI PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PEMPEK (STUDI KASUS UMKM PEMPEK MASAYU 212 KOTA JAMBI) - Rusdiana Pertiwi G. (Jurnal Dinamika Manajemen, 2016)
This study aims to analyze the effect of product innovation and price on purchasing decisions of Pempek Masayu 212 in Jambi City. The population in this study were Pempek Masayu 212 consumers with 100 respondents. The data collection technique used was a questionnaire. The analytical tools used in this study are instrument tests consisting of validity and reliability tests, multiple regression analysis, t-test, F-test, and coefficient of determination test. The entire analysis was calculated using the SPSS version 22 program. The results of this study indicate that product innovation and prices partially or simultaneously have a positive and significant effect on the purchasing decision of Pempek Masayu 212.